2021
DOI: 10.1016/j.psj.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary green tea powder supplementation enriched egg nutrients and physicochemical property in an indigenous chicken breed

Abstract: Dietary supplementation of green tea changes the antioxidative capacity of chickens. However, the effect of green tea supplementation in the diet on egg quality and the consequent change in processing capacity is still not well known. The aim of this study was to determine whether green tea powder ( GTP ) supplementation could affect egg quality, egg antioxidant capacity, and sensory and egg processing characteristics. Huainan partridge chickens (1,080) at 20 wk old were divided into 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The use of GTP as a feed additive in laying hens' diets to improve albumen quality have been widely reported (72,132,133). Positive effect of tea polyphenols on albumen quality have been demonstrated in literature (134).…”
Section: Phytobioticsmentioning
confidence: 99%
“…The use of GTP as a feed additive in laying hens' diets to improve albumen quality have been widely reported (72,132,133). Positive effect of tea polyphenols on albumen quality have been demonstrated in literature (134).…”
Section: Phytobioticsmentioning
confidence: 99%
“…The membrane of the egg is a fibrous structure. It is crucial for the development of ES [21]. Chemically speaking, an ES from a hen has 65.6 percent water, 11.8 % proteins, 11 % fat, and 11.7 % ash.…”
Section: Nutritional Profile Of Essmentioning
confidence: 99%
“…This can boost the absorption of micro minerals, such as calcium, because calcium is converted to an ionic form in an acidic environment, making it more soluble and accessible. The shortchain fatty acids produced during the prebiotic fiber fermentation process, along with the acidic environment they create, cause the mucosal cells to swell, which increases the surface area of the intestine and enhances calcium absorption [18][19][20][21][22][23][24][25].…”
Section: Prebiotics Probiotics and Synbioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the effectiveness of plant sterol-enriched functional foods as a strategy for reducing the risk of cardiovascular diseases (CVDs) [4]. An enriched egg is a food product containing nutrients with health-beneficial properties and could also help prevent CVDs [5].…”
Section: Introductionmentioning
confidence: 99%